On a few benthic hydroids (Cnidaria, Hydrozoa) from the Kerguelen Islands (southern Indian Ocean), including the description of a new species - Cantero, Álvaro L. Peña (Zootaxa, 2022)
A few samples of benthic hydroids from the remote Kerguelen Islands have been studied. The material was collected within the French research program ProteKer in 2013 and 2014. Six species were found in the material, four anthoathecates and two leptothecates; two of the species were identified only to genus level. All species, including Candelabrum bitentaculatum sp. nov., are described and discussed.